2018
DOI: 10.3354/ab00700
|View full text |Cite
|
Sign up to set email alerts
|

Production of enzymes and siderophores by epiphytic bacteria isolated from the marine macroalga Ulva lactuca

Abstract: Macroalgae provide important habitats for microorganisms, with surfaces that are rich in nutrients and a microbial niche for isolation of different bacterial groups. In this study, we evaluated the production of enzymes (amylases, lipases, cellulases and agarases) and siderophores by strains isolated from the macroalga Ulva lactuca growing in the Santa Marta region of the Colombian Caribbean Sea. We taxonomically identified a subset of the bacteria and tested 207 bacterial isolates. Of these, 25 (12%) and 121 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…The enzyme activities in the present study are comparable with the reports of Gonzalez et al (2018) ability to produce extracellular enzymes (Divakaran et al, 2011).…”
Section: Selection Of Potentially Probiotic Strainssupporting
confidence: 90%
“…The enzyme activities in the present study are comparable with the reports of Gonzalez et al (2018) ability to produce extracellular enzymes (Divakaran et al, 2011).…”
Section: Selection Of Potentially Probiotic Strainssupporting
confidence: 90%
“…Sànchez Hinojosa and colleagues (Sánchez Hinojosa et al 2018 ) found that only 12% of their 172 isolates, from three Antarctic macroalgae ( Himantothallus grandifolius , Phaeophyta ; Himantothallus grandifolius and Plocamium cartilaginoum , Rhodophyta ), showed agarolytic activity. In contrast, a study performed on 207 bacterial isolates obtained from the green alga Ulva lactuca , 58% of the isolates produced amylases and/or agarases (Comba González et al 2018 ). Low prevalence of PD isolates could depend on the utilization of healthy algal specimens, where the presence of bacteria capable of degrading cell wall components, dangerous for algal well-being and maintenance, is controlled and limited by the presence of other macroalga-associated bacteria (Hollants et al 2013 and references therein).…”
Section: Discussionmentioning
confidence: 97%
“…The raw algal material was searched in an area of rockyshore “La Punta de la Loma”, Santa Marta – Colombia, in the intertidal zone, 10 km south of the river Gaira. EPI24 was inoculated according to the methodology proposed in previous research [ 11 ] ( Table 1 ). The bacterium was cultivated in LB agar and incubated at 30 °C for 48 h. The agar plate screening for positive laccase production was performed with three assays with different phenolic substrates (guaiacol, 2,6-Dimethoxyphenol and tannic acid) as described by Dhiman [ 15 ].…”
Section: Data Descriptionmentioning
confidence: 99%
“…Studies of epiphytic bacteria from marine macroalgae of the Ulva genus identified Vibrio, Pseudomonas and Achromobacter genera as representatives of the culturable bacterial community from this macroalga [ 9 ]. Regarding, recent studies have described Gram negative bacteria of the genera Pseudoalteromonas, Shewanella, Halomonas, Roseobacter, Marinomonas, and Vibrio and some Gram positive bacteria such as Bacillus genus, as part of the culturable epiphytic component from Ulva [ [10] , [11] , [12] , [13] , [14] ]. In this study, we obtained a strain belonging to the Achromobacter sp ., being the first record of this genus within the bacterial epiphytes found in U. lactuca sampled in the Colombian Caribbean Sea.…”
Section: Introductionmentioning
confidence: 99%